Allelopathic effect of the weed Cyperus esculentus on the growth of young Pinus patula plantations - Reinhardt, Carl Frederick (Charlie) (University of Pretoria, 2013)
Dissertation (MSc Agric (Weed Science))--University of Pretoria, 2001.